A Comparative Study on the Suitability and Treatment Compliance of an Improved Wristband Wearing Method Compared with the Traditional Method. (28th June 2022) - Wang, Jing; Zhao, Xiaoyan; Huang, Jing; Cao, Xiaoyu; Pan, Shibo; Jin, Hua
Abstract : Background . Wristband identification (wristband for short) is an accurate and reliable tool for patients, and it is the basic requirement of the whole medical activity of the hospital. Wearing wristband correctly can help clinical medical staff to identify patients quickly and accurately and effectively prevent medical errors and medical accidents. According to the survey, the wristband wearing rate of clinical patients is still low, mainly because the wristband is tight and improper and the medical staff education is not in place. Therefore, how to scientifically and effectively improve the wearing rate and accuracy of patients' wristbands is an urgent nursing safety problem to be solved. Accurate identification of children is the key to ensure the safety of clinical drug use and carry out diagnosis and treatment, and wearing wristbands is the main way to identify children. Objective . A case-control study was conducted to explore the suitability and treatment compliance of an enhanced wristband wearing method compared with the traditional method. Methods . 260 hospitalized children admitted to our hospital from March 2019 to June 2021 were randomly divided into control group and study group. The control group used a traditional wristband, while the study group used a modified wristband. The existence of wristbands, the recognition speed of medical staff, the clarity of wristband handwriting, and the incidence of skin depression were observed in the two groups. The local skin reaction, wearing rate, incidence of wristband-related adverse events, identity compliance, and family satisfaction of patients with wristband were compared. Results . In terms of authentication compliance, the normal authentication frequency of the observation group was higher than that of the control group, but the difference was not statistically significant (P > 0.05 ). The score of local skin reaction in the test group was lower than that in the control group, and the skin condition in the test group was better than that in the control group (P < 0.05 ). The incidence of adverse events in the observation group was significantly lower than that in the control group (P < 0.05 ). The proportion of wristband position, immediate recognition, and clear handwriting in the observation group was significantly higher than that in the control group in terms of wristband position, recognition speed, clear handwriting, and sunken skin (P < 0.05 ). There was no significant difference in the incidence of skin depression (P > 0.05 ). Parents' ratings of satisfaction with treatment and child wearing rates were compared. After the intervention, the parents' satisfaction with diagnosis and treatment in the observation group was 89.23%, which was significantly higher than that in the control group (79.23%) (P < 0.05 ). The score of wearing rate in the observation group was significantly higher than that in the control group (P < 0.05 ). Conclusion . On the basis of ensuring children's compliance, the improved wristband wearing method can reduce the incidence of wristband shedding and ligature marks, reduce the diagnosis and treatment error rate, enhance the suitability of wearing, enhance the work efficiency of doctors and treaters, and improve the satisfaction of diagnosis and treatment.